Prediction of Delayed Neurodevelopment in Infants Using Brainstem Auditory Evoked Potentials and the Bayley II Scales - Wang, Xiaoyan; Carroll, Xianming; Wang, Hong; Zhang, Ping; Selvaraj, Jonathan Nimal; Leeper-Woodford, Sandra (Frontiers in Pediatrics, 2020)
Background: Brainstem auditory evoked potentials (BAEP) provide an objective analysis of central nervous system function and development in infants. This study proposed to examine the relationship between infant BAEP values at age 6 months, and their neurodevelopment at age 2 years assessed by the mental development indices (MDI), a form of Bayley Scales of Infant Development. We hypothesized that in infants with BAEP values outside normal range, there may be neurodevelopmental delays, as shown by their MDI scores. Methods: An exploratory investigation was conducted using preterm (28-36 weeks gestation; 95 cases) and term infants (≥ 37 weeks gestation; 100 cases) who were born with specific perinatal conditions. BAEP values were recorded in these infants from 1 to 8 months of age, and compared with MDI scores in these infants at age 2 years. A multivariate linear regressions model was performed to test the associations between all variables and MDI scores. Stratified linear regression was used to test the interactions between gestational age and BAEP values with MDI scores. Significance was determined at a p-value < 0.05. Results: We found that BAEP values were inversely associated with MDI scores in premature infants (β = −1.89; 95% confidence interval = −3.42 to −0.36), and that the effect of gestational age and BAEP values on the MDI scores is decreased by 1.89 points due to the interaction between these two variables. In premature babies, the lower the BAEP value below the mean, the greater the decrease in MDI score at age 2 years. Asphyxia, and lower socioeconomic status in the family were also covariates associated with lower MDI scores at age 2 years. Conclusion: The data provided evidence that BAEP values outside the normal range in premature infants at age 6 months may predict developmental delays in cognitive and motor skills, as shown by MDI scores. We propose that BAEP assessment may be utilized as a potential indicator for neurodevelopment, and suggest that early intellectual and public health interventions should be encouraged to enrich neurodevelopment in premature babies with BAEP values outside the normal range.